2012
DOI: 10.1111/j.1365-313x.2011.04891.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles of two growth‐inhibiting rhizobacteria commonly engage AtWRKY18 function

Abstract: SUMMARYInteractions with the (a)biotic environment play key roles in a plant's fitness and vitality. In addition to direct surface-to-surface contact, volatile chemicals can also affect the physiology of organism. Volatiles of Serratia plymuthica and Stenotrophomonas maltophilia significantly inhibited growth and induced H 2 O 2 production in Arabidopsis in dual culture. Within 1 day, transcriptional changes were observed by promoter-GUS assays using a stress-inducible W-box-containing 4xGST1 construct. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 78 publications
1
95
0
1
Order By: Relevance
“…Studies in plant response to pathogens showed that WRKY60 may function through interaction with WRKY18 and WRKY40 to promote or decrease their binding affinities to the promoters of their target genes (Xu et al , 2006; Shen et al , 2007; Wenke et al , 2012). Consistently, in this study, we showed that WRKY18, WRKY40 and WRKY60 transcription factors cooperatively repress CRK5 gene expression (Figs 10–12).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in plant response to pathogens showed that WRKY60 may function through interaction with WRKY18 and WRKY40 to promote or decrease their binding affinities to the promoters of their target genes (Xu et al , 2006; Shen et al , 2007; Wenke et al , 2012). Consistently, in this study, we showed that WRKY18, WRKY40 and WRKY60 transcription factors cooperatively repress CRK5 gene expression (Figs 10–12).…”
Section: Discussionmentioning
confidence: 99%
“…Two replicates per genotype were used for ATH1 GeneChip (Affymetrix) analyses. Sample preparation, copy RNA synthesis, and quality controls were performed as described before (Wenke et al, 2012). The Affymetrix CEL files were imported into GeneSpring GX software version 7.3 (Agilent Technologies).…”
Section: Microarray Hybridization and Data Processingmentioning
confidence: 99%
“…Two biological replicates per genotype were grown for the microarray analyses. Sample preparation for ATH1 GeneChips was performed exactly as described previously (Wenke et al, 2012).…”
Section: Transcriptional Profilingmentioning
confidence: 99%